The Declaration of Nullity of Marriage Due to Force and Grave Fear in the Diocese of Ruteng, Indonesia and Its Implication to Premarital Pastoral Care: Case Studies 2012-2022 - Jehaut, Rikardus Moses; Dahurandi, Keristian; Tolo, Paulus (Universitas Negeri Semarang, 2024)
This article aims to examine the issue regarding the declaration of nullity of marriage in the Ruteng Diocese based on coercion and serious fear in the 2012-2022 period. By using qualitative methods with a literature study approach, the author tries to collect and analyze data obtained from various sources, especially diocesan Tribunal documents as the main reference, and other sources that are relevant and support the author’s argument. The results of this research show that compared with other cases, the number of declarations of nullity of marriage in the Ruteng Diocese based on force and grave fear in the past 10 years is very high. This coercion and serious fear is caused, among other things, by family pressure, threats of physical violence and murder, threats of cutting off one’s genitals, and threats of suicide. The author argues that this problematic fact carries certain implications for pre-marital pastoral care. Serious attention to marriage preparation courses and canonical inquiry as part of pre-marital pastoral care is essential as an instrument for detecting defects of consensus.